2022
DOI: 10.1039/d1bm02017j
|View full text |Cite
|
Sign up to set email alerts
|

Protein-mediated DNA self-assembly by controlling the surface charge in a molecular crowding environment

Abstract: Designing and building artificial nanodevices and nanoarchitectures in living systems are extremely intriguing subjects in nanotechnology and synthetic biology. Taking advantage of cellular machinery and endogenous biomacromolecules, such as proteins,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…As PEI is highly positively charged, the introduction of TH buffer into the assembly system can not only confine the charge status of PEI to a mild level but also avoid any potential hydrolysis of DNA at a high pH. 23 The formation of PNT was initially analysed using polyacrylamide gel electrophoresis (PAGE). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As PEI is highly positively charged, the introduction of TH buffer into the assembly system can not only confine the charge status of PEI to a mild level but also avoid any potential hydrolysis of DNA at a high pH. 23 The formation of PNT was initially analysed using polyacrylamide gel electrophoresis (PAGE). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, those enhanced characteristics, especially in photothermal and photoluminescence, and Raman scattering performance of MoS 2 nanohybrids could significantly promote the bio-sensing and therapy applications. [107][108][109] Author contributions Na Zhang: writing -original draft, investigation. Ying Jie Zheng: writing -original draft, investigation.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Moreover, those enhanced characteristics, especially in photothermal and photoluminescence, and Raman scattering performance of MoS 2 nanohybrids could significantly promote the bio-sensing and therapy applications. 107–109…”
Section: Outlook and Horizonsmentioning
confidence: 99%
“…Especially, the DNA-based magnetic materials have attracted increasing attention due to their accurate self-assemblies via noncovalent interactions (H-bonding, π–π stacking, etc. ). , However, the natural DNA nucleobases have some limitations in functional applications: (i) there are only four DNA nucleobases in nature, and they do not possess magnetic properties; (ii) they have two types of structural units resulting from the fixed pairing mode. , So the development of well-ordered structures with efficient magnetic coupling properties by the modification and transformation of nucleobases has been pursued. For example, Bu and Zhao revealed that the DNA nucleobases are functionalized by nitroxide diradicals, which are promising for building blocks of the biomimetic magnetic nanodevices or nanomaterials.…”
Section: Introductionmentioning
confidence: 99%